Analysis of the thermal performance of heat exchangers for active chilled beam units - Domínguez-Muñoz, Fernando; González Espín, José Luis; Coronas Salcedo, Alberto; Cejudo-López, José Manuel (My University, 2018)
Coils used in active chilled beams (ACB) have some distinctive features compared to conventional coils used in fan-coil units. On the air side, the flow rate of induced air is limited and air velocities are thus much lower than those prevailing in fan-coils. Consequently, most of the correlations available in the open literature to calculate the convection coefficient on the air side are out of range when applied to ACB coils. In addition, the nature of the induction process causes some degree of non-uniformity in the air distribution over the coil. On the liquid side, circuitry can also be distinctive due to space constrains or functional requirements. Some commercial products use one circuit arrangements (all tubes connected in series) with different possible flow paths; two or more circuit schemes are also frequent. In this paper, ongoing research on active chilled beam modeling is presented. A generic numerical model of plate fin-and-tube heat exchanger is briefly described along with a test bench in which several ACB units have been tested. Experimental data for an example coil is used along with the coil model to determine a correlation for the air-side heat transfer. The calibrated numerical model is then used to simulate the coil
Keywords: Intercambiadores de calor; ACB; Effectiveness-NTU; Heat exchangers